ANALYSIS AND SOLUTIONS OF THE GENDER FACTOR IN THE MANAGEMENT OF THE MODERN UZBEK URBAN ECOSYSTEM - Khaydarova Khilola Khislatovna (American Journals, 2023)
The article describes the gender relations characteristic of the Uzbek society. The importance of paying special attention to the problems of managing urban ecosystems and a gender approach in their solution is also emphasized. As part of the topic, gender relations in the households of Uzbeks were analysed, as well as the impact of gender relations on the urban ecosystem. In addition, the article examines and analyses the views of scientists on gender approaches.
Keywords: gender, management, city, urban ecosystem, own territory, foreign territory.